Unidirectional quantum key distribution system based upon a time-division Mach-Zehnder interferometer consisting of phase stabilized optical fibers - Park, Jun-Bum; Khym, Sungwon; Lee, Kyung-Woon; Shin, Hyun-Joon; Moon, Sung (IOP PUBLISHING LTD, 2008)
We propose a unidirectional quantum key distribution (QKD) system based upon a time-division Mach-Zehnder interferometer (MZ) using phase stabilized optical fibers (PSOFs) for the sake of achieving the phase stability during the key distribution. A simple comparison between MZs constituent with PSOF and normal single mode fiber (SMF) is made. During the key distribution over 25 km of standard optical fiber, the phase drift of 4.6 x 10(-4)pi/s is obtained. We discuss the demonstration of the quantum key distribution when the asymmetric MZ (AMZ) of PSOF is applied on the proposed QKD system.
Keywords: SINGLE-PHOTON INTERFERENCE; CRYPTOGRAPHY; DETECTORS; LONG